Geum rubrum comb. nov. (Rosaceae), elevation of Geum elatum forma rubrum to species rank - Khuroo, Anzar Ahmad; Hussain, Khalid; Gulzar, Ruquia; Ganai, Mansoor R. (Phytotaxa, 2022)
Geum elatum forma rubrum (Rosaceae) is elevated here to the rank of species, Geum rubrum comb. nov. from the Himalaya. The species differs from the commonly occurring G. elatum in several distinctive characters which include: smaller flower size (2.2–2.8 cm diameter), elliptic or lanceolate pseudo-sepal, glandular hairs on calyx, red petals, dorsifixed stamens, lesser number of carpels (6–8) and achene size (7.8–8.0 × 1.6–1.8 mm). Based on the morphological study of the fresh plant specimens collected from Kashmir Himalaya, here we provide a detailed description of G. rubrum and photographic illustrations of its diagnostic characters. We also provide comparison of distinguishing features of G. rubrum with its closely related G. elatum to facilitate easier field identification.